2011
DOI: 10.19030/iber.v2i6.3804
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Economics In The K-12 Curriculum

Abstract: This is a multi-year study of the effects of integrating economics into the curriculum on the Maryland School Performance Assessment Program (MSPAP) economics outcome scores. The study was carried out using State summary and disaggregated data and summary data for each school system in the State of Maryland. The 1992, 1994, 1995, 1997 and 2000 MSPAP economics outcome scores for grades 3, 5, and 8, constitute the dependent variable for the study with the level of integration of economics in the curriculum and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Walstad (1979) used a two-stage least-squares approach to investigate the use of a particular teacher in-service program (the Unified Science and Mathematics for Elementary School curriculum) and concluded that intermediate elementary students -appear to improve their economic understanding significantly by working on comprehensive, realistic, and economics-oriented problems‖ (p. 9). Georgiou (2003) showed that integrating economics into the social studies curriculum improved economics outcomes on state assessments, while Walstad and Watts (1985) cautioned that although infusion or integration is a commonly used approach for teaching economics in the elementary grades, time limitations prevent teaching more of the content. If economics can be integrated into mathematics in the elementary school setting, perhaps learning can improve in both areas of content.…”
Section: Improving Mathematics Education By Implementing Economicsmentioning
confidence: 99%
“…Walstad (1979) used a two-stage least-squares approach to investigate the use of a particular teacher in-service program (the Unified Science and Mathematics for Elementary School curriculum) and concluded that intermediate elementary students -appear to improve their economic understanding significantly by working on comprehensive, realistic, and economics-oriented problems‖ (p. 9). Georgiou (2003) showed that integrating economics into the social studies curriculum improved economics outcomes on state assessments, while Walstad and Watts (1985) cautioned that although infusion or integration is a commonly used approach for teaching economics in the elementary grades, time limitations prevent teaching more of the content. If economics can be integrated into mathematics in the elementary school setting, perhaps learning can improve in both areas of content.…”
Section: Improving Mathematics Education By Implementing Economicsmentioning
confidence: 99%